2005
DOI: 10.1007/s00345-005-0024-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 1-day prophylaxis medication with fluoroquinolone for prostate biopsy

Abstract: A prospective, randomized trial in which 236 patients received oral levofloxacin, either at 600 mg/day for 1 day (n = 124) or 300 mg/day for 3 days (n = 112). Urinalysis, plasma white blood cell count (WBC) (per mm3), and C reactive protein (CRP) (mg/dl) levels were checked before prostate biopsy (PBX), on the day after PBX, and on the seventh day after PBX. Two patients (1.61%) who received 600 mg for 1 day and 2 patients (1.79%) who received 300 mg for 3 days had febrile infectious complications. There was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 22 publications
3
41
1
1
Order By: Relevance
“…However, complication by urinary tract infection causing fever greater than 38°C is not uncommon, occurring in 1% to 5% of patients. 4,5,[9][10][11][12] Moreover, some cases of fatal sepsis after biopsy have been reported in Japan. 7,8 However, there is no gold standard for preparing a patient before prostate biopsy, especially regarding the use of antibiotics.…”
Section: Discussionmentioning
confidence: 98%
“…However, complication by urinary tract infection causing fever greater than 38°C is not uncommon, occurring in 1% to 5% of patients. 4,5,[9][10][11][12] Moreover, some cases of fatal sepsis after biopsy have been reported in Japan. 7,8 However, there is no gold standard for preparing a patient before prostate biopsy, especially regarding the use of antibiotics.…”
Section: Discussionmentioning
confidence: 98%
“…They found that asymptomatic bacteriuria rate was significantly low in the antibiotic group. Recently some randomized controlled trials showed that single or 1-day doses are as effective as 3-day doses [20][21][22] , and currently the American Urological Association recommends to use fluoroquinolone not longer than a day ( ! 24 h) [4] .…”
Section: Discussionmentioning
confidence: 99%
“…This principle is relevant for out-patient settings as well. Several randomized controlled trials have documented the equivalence of single-dose or one-day regimens compared to three-day regimens for TRUSPB [6,18,19]. …”
Section: Discussionmentioning
confidence: 99%